1995
DOI: 10.1007/bf00303812
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar astrocytoma of childhood: long-term follow-up

Abstract: Cerebellar astrocytoma of childhood has always been regarded as a benign tumour. Certain issues still attract debate, in particular the role of radiotherapy as an adjuvant to surgery, management of the cyst wall in cystic lesions and treatment of recurrent tumours. To provide some answers to these questions, the experience in Birmingham (United Kingdom) between the years 1959 and 1991 was reviewed. Ninety-seven patients aged 0-14 years had been treated and the histological material was reassessed independently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 15 publications
6
41
1
Order By: Relevance
“…We did not observe any improvement in prognosis after postoperative radiotherapy like Sgouros et al reported (20), but our number of patients was too small for statistical analysis. We prefer to perform second surgery for patients with residual tumor if it is possible because of the potential risks of radiotherapy.…”
Section: Bilginer B Et Al: Cerebellar Pilocytic Astrocytomas In Chilcontrasting
confidence: 51%
See 1 more Smart Citation
“…We did not observe any improvement in prognosis after postoperative radiotherapy like Sgouros et al reported (20), but our number of patients was too small for statistical analysis. We prefer to perform second surgery for patients with residual tumor if it is possible because of the potential risks of radiotherapy.…”
Section: Bilginer B Et Al: Cerebellar Pilocytic Astrocytomas In Chilcontrasting
confidence: 51%
“…Sgouros et al (20) reported that the outcome in cystic tumors is not so much different between total and subtotal resections. Pencalet et al (16) reported that they remove any macroscopically apparent abnormal cyst wall because of the risk of recurrence.…”
Section: Bilginer B Et Al: Cerebellar Pilocytic Astrocytomas In Chilmentioning
confidence: 99%
“…Even in the setting of documented should residual, many tumors remain indolent. After imaging confirmed GTR, recurrence is uncommon, noted at 5% to 10% in major series (206,207,208). After incomplete resection, disease progression has been reported in 30% to 60% of cases at 5 years or more, long term survival remains above 65% (205,206,209).…”
Section: Surgerymentioning
confidence: 99%
“…Malignant gliomas are quite uncommon in the childhood cerebellum. The median age at diagnosis is 5 to 6 years, with 20% of cases younger than 3 years; astrocytomas of this location are rarely found in infants (206,207). Presenting symptoms often are confined to those associated with elevated intracranial pressure, with less frequent altered cerebellar function; cranial nerve deficits are uncommon.…”
Section: Cerebellar Astrocytomasmentioning
confidence: 99%
See 1 more Smart Citation